Nurses' Involvement in Health Policy Development and Analysis: Examining the Perspectives of Nurse Managers - Agyepong, Edith Biamah; Ofei, Adelaide Maria Ansah; Okyere, Enoch Danso; Ocloo, Vida (Universitas Airlangga, 2023)
Introduction: Nurses make critical decisions that affect the lives of clients. This necessitates their involvement in health policy development to enhance the quality of care delivered to clients. However, only a handful of nurses get the opportunity to participate in developing policies that border on nursing. This study intended to discover nurse managers' knowledge of policy formation, their involvement in health policy formulation, and the challenges they encounter in their quest to participate in policy formulation. Method: The study employed the qualitative approach with an exploratory descriptive design using individual interviews with 12 nurse managers purposively selected for the study. Results: The findings from the study indicated that nurse managers play an important role as major stakeholders in policy development since they work with nurses and clients. Also, disunity among nurses was identified as a major barrier to nurses' involvement in policy development. Conclusions: The study reveals nurses' strong interest in policy involvement, hindered by perceived knowledge gaps, limited education access, and dominance of other professionals in policy roles. Addressing these challenges requires investing in education, political advocacy, and establishing a dedicated nursing unit for policy influence, supported by integrated policy education and interdisciplinary collaboration.